The development of human capital in Ukraine: global influences and tendencies - Smirnova, І.; Simakov, K. (Економічний вісник Донбасу, 2018)
The problems of development of human capital are considered and the preconditions for ensuring its competitiveness in Ukraine are determined. The position of the country in the index of global competitiveness and human capital and its components is investigated. It is determined that the indicator of efficiency of human capital exploitation in Ukraine is the lowest because of the lack of a system of commercialization of technologies. The reasons for the outflow of human capital from Ukraine to the EU countries are determined and ways of overcoming the emigration are proposed. It is proved that in order to ensure the quality of human capital and intensify investment in its development in Ukraine it is necessary to promote the process of innovation development in educational institutions, supplemented by its introduction of innovative technologies in the field of higher education; provide training in accordance with the modern requirements of employers for their mobility, the ability to generate new ideas and readiness to innovate within the strategic objectives of the enterprise.